PENGARUH KELOMPOK REFERENSI TERHADAP KEPUTUSAN BERKUNJUNG DIKAWASAN WISATA KULINER PANTAI KOLO - Sri Ernawati zunaidin; Harry Nurdin; Sulhaini Sulhaini (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
This study aims to determine the influence of reference groups on the visit decision to the Kolo beach culinary tourism area. The type of research used is associative, the research location is in the City of Bima. The population in this study were all consumers who had visited the Kolo beach culinary tourism area, the sample in this study amounted to 100 people with purposive sampling technique. The research instrument uses a questionnaire with a Likert scale measurement. The type of data used in this study is quantitative data with research data sources, namely primary data. Data collection techniques are observation, questionnaires/questionnaires and literature study. Data analysis used simple linear regression. The results showed that the Reference Group had an effect on the visit decision to the Kolo beach culinary tourism area